Design, synthesis and cytotoxic evaluation of novel betulonic acid-diazine derivatives as potential antitumor agents - Shu, Yisong; Li, Feifei; Han, Yaotian; Wang, Penglong; Gao, Feng; Yan, Mengmeng; Liang, Miao; Ma, Qiang; Zhang, Yuzhong; Ding, Xia; Lei, Haimin (Frontiers in Chemistry, 2022)
With the purpose to improve antiproliferative activity, 26 new betulonic acid-diazine derivatives were designed and synthesized from betulinic acid. The anticancer activity of these semi-synthetic compounds was evaluated by MTT assay in both tumor cell lines and normal cell line. The results indicated that majority of new compounds exhibited improved antitumor activity compared with the parent compound betulonic acid. Compound BoA2C, in particular, had the most significant action with IC50 value of 3.39 μM against MCF-7 cells, while it showed lower cytotoxicity on MDCK cell line than cisplatin. Furthermore, we discovered that BoA2C strongly increased MCF-7 cell damage mostly by influencing arginine and fatty acid metabolism. In addition, the structure-activity relationships were briefly discussed. The results of this study suggested that the introduction of different diazines at C-28 could selectively inhibit different kinds of cancer cells and might be an effective way to synthesize potent anticancer lead compound from betulonic acid.